Effects of grazing exclusion and shrub encroachment on the ecosystem ecology of evergreen oak woodland - Lecomte, Xavier Jean François (2018)
Doutoramento em Engenharia Florestal e dos Recursos Naturais - Instituto Superior de Agronomia